PERANCANGAN SISTEM BERBASIS FUZZY LOGIC UNTUK DEDUPLIKASI PENUNJANG KEPUTUSAN KELAYAKAN NASABAH PADA LEASING PT. CS FINANCE - Sarwo Sarwo; Wiwit Wiwit (Sekolah Tinggi Teknik - PLN, 2015)
Credit general , individual , selective and aimed at enhancing the natural flowering entities on leasing financing in PT . CS Finance , feasibility analysis in the credit decision-making is very influential in the business policy of the company , in the process of the feasibility of the customer on the PT . CS Finance based on the criteria set by the policy principles creditpolicy ( 5C ) . The current manual process mansih authors build intelligent systems based retrieval fuzzylogic for customer eligibility decisions and so the level of accuracy in decision making increases. The programming language used is Java and MySQL database . fuzzylogic application of basic concepts in this research to build intelligent systems to process information resulting in a more humane decision .